Świadectwo w argumentacji za wiarygodnością chrześcijaństwa - Mastej, Jacenty (Verbum Vitae, 2015)
The aim of the article is to demonstrate the significance of testimony in the argumentation for the credibility of Christianity. The issue was presented in five paragraphs. First, the need for the necessary grounds for the credibility of Christianity were laid out. Second, faith as a personal experience of the encounter between men and God is presented. Third, the ecclesial character of testimony is expounded upon. Fourth, a section deals with the issue of recognizing the testimony. Fifth, the motivational value of testimony is considered. Taken together, the analysis demonstrates that Christian testimony, a fruit of living faith, is a sign for the world, pointing to the person of Jesus Christ. Christian lifestyle begs the question about the motives of Christian behavior and is the starting point in martyrological argumentation for the credibility of Christianity.